On-grid Photovoltaic Power System for Governmental Office Electrification - Ali Nasser Hussain; zuhair sameen shuker; Majid Khudair Abbas Al-Tamimi; Mimouna Abid (Journal of Techniques)
Solar energy is one of the most promising renewable energy sources. The potential solar energy has a capacity to meet all energy requirements for human survival on planet earth. Some applications such as a thermoelectric generator, electric power generation with the assistance of solar panels and water applications are required to reduce the demand for electricity generated by conventional power plants. The current work evaluates the effectiveness of solar energy for supplying the police building located in Diyala, Iraq. The installed renewable power system consists of photovoltaic/ battery system set with grid connection installed on the roof of the building with a capacity of 5.52 kWp and battery unit (200 A, 48 Volt). Based on the daily average load kWh and daily average solar irradiance for the selected site (4.3 kWh/m2), the results of the energy generated by the system for two selected days showed that for a sunny day is about (11.63 kWh) and for party cloudy day is about (8.02 kWh). The average of energy fed to the grid for a sunny day was recorded more by more than 3.0 kWh and for party cloudy day by more than 4.0 kWh.  The system installed at the first day of February of the year 2021. The obtained results encourage to install of photovoltaic systems in the selected site which can feed such facilities with renewable energy and deliver energy to the grid.